Bacterial Consortia as a Sustainable Alternative to Jute Batching Oil (JBO) in Jute Yarn Manufacturing Process - Md. Rezaul Karim Rana; Rabeya Rabeya; Al Amin; Farzana Haque Shaon; Farhana Tasnim Chowdhury; Haseena Khan; Mohammad Riazul Islam (Journal of Fibers and Polymer Composites, 2026)
Jute fiber used in the production of yarn is traditionally treated with a 2% emulsion of jute batching oil (JBO) to reduce stiffness and improve processability. However, due to the high cost and potential carcinogenic effects of JBO, there is a pressing need for alternative methods. This study investigates the use of a microbial consortium to achieve a cost-effective and eco-friendly reduction of JBO use in yarn production. A total of 51 bacterial strains were isolated from JBO-treated jute fiber at Janata Jute Mills, with 17 strains exhibiting significant growth in 2% JBO. After excluding duplicates, potential pathogens, and strains with endoglucanase activity, a final consortium of nine bacteria was established. The physical properties of jute fiber treated with this consortium alongside varying concentrations of JBO (1% and 2%) were analyzed over different incubation periods. Results indicated that treatment with 1% JBO and the bacterial consortium produced comparable effects on temperature and moisture regain to the control group (2% JBO). Notably, fibers treated with the consortium exhibited enhanced elasticity, showing a 46.6% increase in maximum pressure and 12.2% increase in extension at breakage compared to the control (2% JBO). Additionally, wastage during processing was reduced by 24.1% for breaker card processing in the treated group. Scanning electron microscopy (SEM) revealed a rough surface morphology in the treated fibers, indicative of biofilm formation. This study suggests that employing microbial consortia with reduced JBO concentrations offers a promising alternative for enhancing fiber quality in jute yarn manufacturing while promoting environmentally sustainable practices.